Dataset associated with “What’s in a name? The paradox of citizen science and community science” - Lin Hunter, Danielle; Newman, Gregory; Balgopal, Meena (Colorado State University. Libraries, 2021)
Citizen science has expanded ecological and environmental sciences by making possible studies across greater spatial and temporal scales while incorporating local expertise and interests that might otherwise be overlooked. Broadly, citizen science involves the public in the process of science. However, it continues to struggle to engage diverse participants. Citizen science project coordinators are increasingly trying to promote inclusivity by rebranding as “community science” to avoid the term “citizen.” Rebranding efforts, while well-intentioned, are uninformed by research, as we lack an evidenced-based understanding of these terms. We distributed a survey to those who participate in citizen and community science. We found differences in how well known and accepted the terms are, who is perceived as initiating and benefiting from the projects, and associated levels of inclusivity. Our findings have important implications for those involved in citizen and community science seeking to better describe projects in the future.
The dataset contains survey data collected from those involved in citizen and community science. It was collected to determine differences in how this community perceives the terms "citizen science" and "community science." It includes two files: a README file and a spreadsheet contain the data.
Department of Biology
Graduate Degree Program in Ecology
Natural Resource Ecology Laboratory (NREL)
Keywords: citizen science; community science; inclusivity; diversity; environmental communication; science communication; evidence-based practice